0714 Population-Level Snoring and Probable Sleep-Disordered Breathing Associated with Greater Sedentary Activity. (25th May 2022) - Abdi, Harun; Mason, Brooke; Wills, Chloe; Tubbs, Andrew; Killgore, William; Grandner, Michael
Abstract: Introduction: Increased frequency of snoring can be an indicator of sleep-disordered breathing, which is associated with a myriad of comorbidities, including increased cardiovascular disease risk. Previous studies have shown that sleep-disordered breathing is associated with less physical activity, but few studies examined this at the population lavel, or relative to primary snoring. Methods: This analysis used a linear regression analysis on the 2017- March 2020 data collected from the National Health and Nutrition Examination Survey (NHANES) to explore the relationship between the minutes of sedentary activity and the frequency of snoring. Participants were asked how often they snored in the last 12 months. Responses were categorized as "Never", "Rarely– 1-2 nights/week", "Occasionally– 3-4 nights/week", or "Frequently– >=5 nights/week." Self-reported sedentary activity was measured in minutes during a typical day. A modified STOP-BANG score was created based on NHANES measures of snoring, daytime tiredness, snorting/gasping during sleep, hypertension, body mass index, age, and gender (no measure of neck circumference). Reported results were unweighted; weighted results forthcoming. Results: Significant unadjusted results indicate that those who reported snoring frequently had 19.2 minutes more sedentary time ([7.98, 30.4], p<0.0001); and those with estimated sleep apnea had 16.2 more minutes of sedentary time than those without sleep apnea ([7.19, 25.2], p<0.001). When adjusted for sex, age, race, education level, and marital status, the estimated difference between frequent snorers and those that reported never snoring increased to 35.9 minutes of more sedentary activity ([24.4, 47.3], p<0.0001) a day. After adjusting for covariates, those with probable sleep apnea showed 43.9 more minutes of sedentary activity compared to those without sleep apnea ([34.1, 53.6], p<0.001). Conclusion: Overall, those who snore frequently (5 or more nights a week) or have a high risk of sleep apnea show a larger number of sedentary minutes per day then those that don't snore or have probable sleep apnea. These relationships may be bidirectional, and directionality should be addressed in future studies. Support (If Any):